Activated Bentonite Modified-Carbon Paste Electrode for Determination The Level of Copper Ion (Cu2+) in Tomato - Irdhawati Irdhawati; Ekki Inur Ingtyas Mawarni; Ayu Jyostosya Yotirani Arya Wijana; Feby Silvia Sitio; Ni Putu Gita Widi Saraswati; Emmy Sahara (Graduate Program of Syiah Kuala University, 2020)
Voltammetry is an electroanalytical method measure current as a function of applied potential. The working electrode in the voltammetry method dramatically affects the result of the electrochemical analysis. Modification of the working electrode can improve measurement performance. In this research, the carbon paste electrode (CPE) was modified with Bentonite (CPEB) to determine copper's level using differential pulse voltammetry technique. CPE and CPEB were used as working electrodes, handmade Ag/AgCl as a reference electrode, and Pt wire as the counter electrode. The measurement parameters were optimized, including the composition of bentonite in carbon paste and scan rates. Furthermore, the measurement conditions were validated, involved linear concentration range, detection limit (LoD), the limit of quantization (LoQ), repeatability, and recovery. The results showed that bentonite's optimum composition was 40% of the total weight of graphite and activated bentonite. The scan rate optimum for Cu2+ measurement was obtained at 20 mV/s with CPE and became faster to be 25 mV/s with CPEB. The linearity of the standard solution measurement of Cu2+ using CPE was in the range of 5 to 100 μg/L and changed to 5 to 500 μg/L using CPEB. LoD and LoQ values of standard solution Cu2+ measurement with CPEB were slower than CPE. The Horwitz ratio calculation was smaller than two for both CPE and CPEB. The recovery of Cu2+ standard measure in sample solution as the matrix was obtained 93,49 ± 6,39%. According to the Decree of the Ministry of Health Number, the level of Cu2+ in the tomato sample was found 6.019 ± 0.69 mg/kg, which is over than threshold value of Cu2+ (5 mg/kg) 03725/B/SK/VII/89.